Bioaccumulation of selected macro- and microelements and their impact on antioxidant properties and accumulation of glucosinolates and phenolic acids in in vitro cultures of Nasturtium officinale (watercress) microshoots. (1st December 2019) - Klimek-Szczykutowicz, Marta; Szopa, Agnieszka; Blicharska, Eliza; Dziurka, Michał; Komsta, Łukasz; Ekiert, Halina
Highlights: Watercress microshoots are able to effectively accumulate macro- and microelements. Bioaccumulation of elements influence the production of glucosinolates and phenolic acids. Bioaccumulation of elements improves the antioxidant potential of biomass. Nasturtium officinale biomass can be used as an 'enriched food'. Abstract: The study evaluated bioaccumulation capacity of macro- and microelements, their impact on the production of glucosinolates and phenolic acids and antioxidant properties in a microshoot culture model of Nasturtium officinale . Elements: calcium, chromium, copper, iron, lithium, magnesium, selenium and zinc were supplemented in different salt concentrations to culture media. Bioaccumulation of elements [mg/100 gDW] varied from 1.24 (Li, 1 mg/l) to 498.62 (Cr, 50 mg/l) and was dependent on the type of element and its concentration. The bioconcentration factor (BCF) ranged from 11.37 (Li, 25 mg/l) to 4467.00 (Ca, 1 mg/l). The total glucosinolate contents [mg/100gDW] varied from 108.11 (Cr, 1 mg/l) to 172.90 (Ca, 1 mg/l). The presence of four phenolic acids was confirmed in the microshoots. Their total contents [mg/100gDW] ranged from 19.35 (Mg, 10 mg/l) to 139.21 (Fe, 50 mg/l). The highest antioxidant activity [nM trolox/mgDW], as evaluated by CUPRAC and QUENCHER-CUPRAC methods, was equal to 55.50 (Cu, 1 mg/l) and 161.10 (Li, 5 mg/l), respectively. The results proved good correlations between all studied parameters.